Istihsan Qiyas Khafi Indication of Al-Bazdawi in Contemporary Fatwa in Indonesia - Amir, Amri; Siraj, Firdaus; Bahar, Muchlis; Wiza, Rahmi; Salem Al-Saedy, Ibrahim bin (Media Syari'ah, 2023)
This research aims to analyze Istihsan qiyas Khafi al-Bazdawi as indicated in contemporary fatwas in Indonesia. What is the concept of Istihsan qiyas khafi al-Bazdawi, and how is it relevant to contemporary fatwas in Indonesia? The research method used is descriptive analysis with a literature study approach sourced from journals, websites, books by al-Bazdawi and his lecturers. The results of the research show that Istihsan qiyas khafi al-Bazdawi is a process of intifa' (taking benefits) on a legal object by using qiyas/illat (legal reasons) khafi (hidden) by removing qiyas/illat jali (real reasons in law), and Istihsan Khafi al-Bazdawi's qiyas are considered relevant to a number of contemporary fatwas of the Indonesian Ulema Council (MUI), including: 1) the prosperity of cash waqf Sukuk, 2) the ease of Sukuk Mudharabah, Murabahah, Musyarakah, 3) the ease of Sweb when fasting, 4) the ease of Vaccine injection while fasting